Comparison of immediate vs deferred cytoreductive nephrectomy in patients with synchronous metastatic renal cell carcinoma receiving sunitinib: the SURTIME randomized clinical trial (vol 5, pg 164, 2018) - Bex, Axel; Mulders, Peter; Jewett, Michael; Wagstaff, John; Van Thienen, Johannes V.; Blank, Christian U.; Van Velthoven, Roland; Laguna, Maria del Pilar; Wood, Lori; Van Melick, Harm H. E.; Aarts, Maureen J.; Lattouf, Jean-Baptiste; et al. (American Medical Association, 2019)
[Abstract Not Available]
Keywords: Clinical; Metastatic Renal Cell Carcinoma; Cytoreductive Nephrectomy (CN)